Legal analysis of civil law settlement in the perspective of criminal legal settlement (Case study of Military Court Decision I-05 Pontianak Number: 46K/PM.I-05/AD/IX/2021) - Indra Jaya; Parluhutan Sagala; M. Ali Ridho (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the interaction between civil law settlements and criminal law settlements in the Indonesian military justice system, focusing on the implications of Military Court Decision I-05 Pontianak Number 46K/PM. I-05/AD/IX/2021. This study explores the complexity of overlapping jurisdictions and their effects on the rights and obligations of the parties involved. Research Methodology: The research method used is a conceptual approach with a normative analysis of laws and regulations, relevant legal practices, and library research. The conceptual approach is intended to analyze legal materials so that the meaning contained in legal terms can be understood. Results: The findings show that criminal proceedings significantly influence civil dispute resolution, particularly in determining liability and shaping civil court decisions. Conversely, the outcomes of civil cases may also affect criminal proceedings when overlapping elements exist. This case study demonstrates how fraud rooted in debt relations blurs the boundaries between civil and criminal domains, creating legal uncertainty. Conclusions: There is a strong need for harmonization and coordination between civil and criminal legal systems to prevent overlapping jurisdictions and ensure fairness. Integrating compensation claims into criminal trials can provide more efficient and comprehensive justice. Limitations: This study is limited to a single military court decision, which may restrict generalization to other jurisdictions and legal contexts. Contribution: This research contributes to legal scholarship by clarifying the interaction between civil and criminal dispute resolution and offers practical recommendations for policymakers, military judges, and practitioners to strengthen legal certainty and justice in Indonesia’s dual legal system.